The Role of Post Harvest Handling on Rice Quality in Indonesia - Dewa Ketut Sadra Swastika (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2012)
IndonesianBeras berfungsi sebagai makanan pokok dan bahan baku berbagai produk pangan lainnya yang memerlukan kualitas tertentu. Perbaikan kualitas beras tidak memberikan insentif bagi petani dan pedagang di Indonesia, khususnya melalui perontokan, pengeringan, dan penggilingan. Di pihak lain, sebagian besra negara-negara penghasil padi member perhatian lebih pada peningkatan kualitas beras. Kualitas beras meliputi sifat-sifat fisik yang mempengaruhi penampilan maupun sifat-sifat kimia yang menentukan kualitas jika dimasak. Proses produksi, pasca panen, penggilingan dan pemasaran mempengaruhi kualitas beras. Peningkatan kualitas beras akan menguntungkan produsen maupun konsumen beras. Agar pedagang beras bersedia melakukan pasca panen secara baik diperlukan insentif harga yang memadai untuk gabah kering giling dan beras, misalnya harga pembelian oleh pemerintah. Teknologi pasca panen juga harus diperbaiki agar kualitas beras yang dihasilkan menjadi lebih baik. EnglishAside from being a staple food, rice also has many uses, especially for food industry. Various rice uses require quality evaluation according to the requirement for a specific end use. Whether rice is acceptable for an intended use is determined by quality testing based on a fixed set of criteria. In Indonesia, the main problem of rice quality improvement is the absence of incentive for farmers and traders to improve rice quality, especially through proper threshing, drying, and milling. On the other hands, most rice producing countries are currently paying more attention to the development of post harvest handling and processing to ensure higher rice grain quality. Rice quality is multidimensional. It includes both physical characteristics that influence appearance, and chemical characteristics that determine cooking quality. Thus, rice grain quality is determined by: production process, post harvest handling, milling and marketing techniques. Among rice post harvest handling, proper threshing, drying, milling, and storage are the key points to produce good quality rice. Rice quality improvement is expected to increase national welfare by raising the value of rice to either consumers or producers. In order to encourage rice businessmen to do the proper post harvest handling, there should be attractive price incentives policy for selling dried paddy (GKG) and milled rice (beras). Price incentive could be in the form of government purchasing price (HPP). In other words, there should be an attractive incentive to do a proper threshing, drying and rice milling by using improved technology in order to produce high quality rice.